The effect of Trichostatin A (TSA) on the regulation of Voltage-Gated Sodium Channels (VGSCS) expression by Repressor Element 1 (RE-1)-silencing transcription factor (REST) using MCF-7 human breast cancer cell line - Sudin, Nor Izzaty Mas (Universiti Sains Malaysia, 2014)
The repressor element 1 (RE-l)-silencing transcription factor (REST) mediates the repression of several neuronal genes in non-neuronal cells. REST represses its target gene through histone deacetylation, chromatin remodeling and methylation. Voltage-gated sodium channels (VGSCs) especially the neonatal Nav1.5 (nNav1.5) is predominantly and highly expressed in aggressive breast cancer. Trichostatin A (TSA), an antifungal antibiotic with cytostatic and differentiating properties in mammalian cell culture, is a potent and specific inhibitor of histone deacetylase (HDAC) activity. Hence, this study is aimed to investigate whether an inhibition of histone deacetylation using TSA is sufficient to induce or enhance REST target genes, Syanatophysin (SYP), Chromogranin A (CHGA) and VGSC (Nav1.5 and nNav1.5) transcription in the weakly metastatic MCF-7 cells. MCF-7 cells were treated with TSA at various concentrations (10, 100, 1000 and 10000 ng/ml) for 24, 48 and 72 h. Then, MCF-7 cells viability were determined by a 3-(4,5-dimethtyl-2-thiazolyl)-2H-tetrazolium bromide (MTT) assay. To investigate the effects of TSA on the expression of genes (REST, SYP, CHGA, Nav1.5 and nNav1.5), total RNA extraction, cDNA synthesis, Polymerase Chain Reaction (PCR) and gel electrophoresis were conducted. MTT assays revealed that TSA inhibited the growth of MCF-7 cells in a dose- and time-dependent manner. TSA caused an increased pattern of SYP and CHGA genes expression dose- and time-dependently. There was a decreased pattern of Nav1.5 gene expression after treatment with TSA compared to control cells. Interestingly, there was an increased pattern of nNav1.5 gene expression after TSA treatment. The findings demonstrate that TSA induced loss of REST repression through histone deacetylation inhibition which caused REST target gene CHGA and SYP to increase. A possibility that nNav1.5 in breast cancer cells are regulated by REST could be postulated when TSA caused a slight increase in its expression, though further works are needed to confirm the interaction.